High-adhesion LED-UV metal printing ink and preparation method thereof

By using surface modification nanocomposite powder and composite anti-aging agent in metal printing inks, the problems of insufficient adhesion and easy aging on special metal substrates are solved, and high adhesion and aging resistance are achieved.

CN119570307APending Publication Date: 2025-03-07ZHONGSHAN FUREY PRINTING MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411803148.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional metal printing inks do not have enough adhesion on special metal substrates and are prone to ultraviolet aging, resulting in unstable appearance and function of the printed material and short service life.

Method used

Nanocomposite powder is prepared by tetrabutyl titanate and zinc nitrate hexahydrate, and modified by sodium silicate and cerium sulfate, the surface modification nanocomposite powder and composite anti-aging agent in the ink are increased, and the adhesion and ultraviolet resistance of the ink are improved.

Benefits of technology

It significantly improves the adhesion and UV aging resistance of the ink, extends the service life of the printed material, and reduces maintenance and replacement costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570307A_ABST
    Figure CN119570307A_ABST
Patent Text Reader

Abstract

The invention provides high-adhesion LED-UV metal printing ink and a preparation method thereof, and belongs to the technical field of ink. The preparation method comprises the following steps: preparing the surface modified nano composite powder; preparing a composite anti-aging agent; preparing an acrylate prepolymer; preparing a modified prepolymer; mixing to prepare the printing ink. The preparation method comprises the following steps: preparing nano-composite powder with ultraviolet resistance from tetrabutyl titanate and zinc nitrate hexahydrate as raw materials, blending the nano-composite powder into slurry, adding a sodium silicate solution and cerous sulfate, carrying out a reaction, carrying out surface modification on the nano-composite powder, inhibiting the photocatalytic activity of the nano-composite powder, and carrying out surface modification on the nano-composite powder. After the anti-aging agent is added into the ink, the anti-aging performance of the ink can be effectively improved, and the anti-discoloration performance of the ink can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inks, and in particular to a high-adhesion LED-UV metal printing ink and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, metal printing is increasingly used in many fields such as packaging, decoration, and electronic equipment casings. Traditional metal printing processes often face some technical difficulties, such as insufficient adhesion of ink on the metal surface and difficulty in effectively resisting ultraviolet aging. These problems seriously limit the quality and service life of metal printing products. In recent years, LED-UV curing technology, as a new type of efficient, environmentally friendly and energy-saving curing method, has gradually been widely used in the field of metal printing inks.

[0003] For some special metals or specially treated metal substrates (such as stainless steel, aluminum alloy anodized surface, etc.), due to the high surface energy and smoothness of the metal surface, it is difficult for traditional metal printing inks to form effective chemical bonds or physical anchoring with them, so it is difficult to form a strong adhesion. In the subsequent processing and use process, the ink is prone to fall off and peeling, affecting the appearance and functional integrity of the printed product. In addition, for metal printed products that are exposed to light outdoors or for a long time, such as billboards, architectural decorative metal components, and automotive parts logos, traditional inks are prone to aging due to ultraviolet radiation. The high-energy photons in ultraviolet rays can cause chemical changes such as chemical bond breakage, oxidation reaction, and molecular chain degradation in the ink, which will lead to a series of problems such as fading, discoloration, gloss reduction, hardness reduction, and poor adhesion of the ink. After a period of ultraviolet irradiation, the originally bright and beautiful printed pattern will become dull and even cracked, powdered, and other serious damage, which greatly shortens the service life of metal printing products and increases maintenance and replacement costs.

[0004] At present, in order to improve adhesion, the method of pre-treating the metal surface is usually adopted, such as chemical etching, primer coating, etc., but these methods increase the process steps and costs, and may cause certain pollution to the environment. In the improvement of ink formula, special adhesion promoters are added, such as silane coupling agents, phosphate compounds, etc., to enhance the bonding between ink and metal, but different adhesion promoters have different applicability to different metals, and the applicability is poor; in anti-aging research, the focus is on adding UV absorbers, hindered amine light stabilizers and other anti-aging agents to improve the UV resistance of ink. However, a single anti-aging agent is often difficult to meet the requirements under long-term, high-intensity ultraviolet irradiation, and UV-resistant materials, such as titanium dioxide, have strong photocatalytic activity and are easily oxidized by organic matter under ultraviolet irradiation, causing it to deteriorate.

[0005] Therefore, it is necessary to provide a high-adhesion LED-UV metal printing ink that is resistant to aging and discoloration and a preparation method thereof to extend its service life. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-adhesion LED-UV metal printing ink and a preparation method thereof.

[0007] A method for preparing a high-adhesion LED-UV metal printing ink comprises the following steps: S1: Preparation of surface modified nanocomposite powders The nanocomposite powder is prepared by using tetrabutyl titanate and zinc nitrate hexahydrate as raw materials, and then the nanocomposite powder is adjusted into a slurry, and a sodium silicate solution and cerium sulfate are added to react to obtain a surface-modified nanocomposite powder; S2: Preparation of composite anti-aging agent Copper sulfate pentahydrate and kaempferol are dissolved separately, mixed and heated for reaction, and a composite anti-aging agent is prepared; S3: Preparation of acrylate prepolymer The acrylate prepolymer is prepared by reacting polyester polyol, isophorone diisocyanate, hydroxyethyl acrylate, dibutyltin dilaurate and p-hydroxyanisole as raw materials; S4: Preparation of modified prepolymer The acrylate prepolymer is dissolved in toluene, histamine and N,N'-dicyclohexylcarbodiimide are added, heated to react, dried, filtered and distilled under reduced pressure to obtain a modified prepolymer; S5: Mixing and preparation of printing ink The modified prepolymer, isobornyl acrylate, trimethylolpropane triacrylate, photoinitiator, pigment, the surface modified nano composite powder, the composite anti-aging agent and auxiliary agent are fully stirred and mixed to obtain printing ink.

[0008] Furthermore, S1 specifically includes the following steps: S1.1: Add tetrabutyl titanate and zinc nitrate hexahydrate into anhydrous ethanol at a volume ratio of 1:(8-10) and a solid-liquid ratio of 1g:(15-25)mL, respectively, and stir thoroughly to dissolve to obtain a titanium source solution and a zinc source solution; S1.2: Control the molar ratio of Ti to Zn to be 1:(3-5), add the titanium source solution to the zinc source solution while stirring, continue stirring for 20-30 minutes, add deionized water after thorough mixing, and add glacial acetic acid to adjust the pH to 6.6-6.8, continue stirring for 20-30 minutes, and then stand for aging for 8-10 hours to obtain a mixed gel; S1.3: placing the mixed gel in an oven, drying at 80-100°C for 3-5h, and then placing it in a muffle furnace, calcining at 500-600°C for 2-3h, grinding and sieving to obtain a nanocomposite powder; S1.4: Add the above nanocomposite powder into deionized water in a mass ratio of 1:(3-4), ultrasonically disperse for 30-40 minutes, and then add sodium hydroxide to adjust the pH to 9-10 to obtain a nanocomposite slurry; S1.5: Heat the above nanocomposite slurry to 80-90°C and keep it warm, then add 1.2-1.3 mol / L sodium silicate solution while stirring, let it stand for 1-2 hours, adjust the heating temperature to 65-75°C, add cerium sulfate while stirring, let it stand for 4-5 hours, filter, wash and dry to obtain a surface-modified nanocomposite powder.

[0009] Furthermore, S2 specifically includes the following steps: S2.1: Add copper sulfate pentahydrate into deionized water at a solid-liquid ratio of 1 g: (40-50) mL, and stir and dissolve at a rate of 500-600 r / min to obtain a copper sulfate solution; S2.2: Add kaempferol to 75% ethanol solution at a solid-liquid ratio of 1 g: (200-300) mL, and stir thoroughly at a rate of 400-500 r / min to dissolve, to obtain a kaempferol solution; S2.3: Add the above-mentioned kaempferol solution to an equal volume of the above-mentioned copper sulfate solution, stir and mix thoroughly, then add 1 mol / L sodium hydroxide solution to adjust the pH to 7-8, and heat the reaction at 50-60°C for 4-5h. After centrifugal separation, washing and drying, a composite anti-aging agent is obtained.

[0010] Furthermore, S3 specifically includes the following steps: S3.1: Add polyester polyol to toluene, stir thoroughly to dissolve, then add isophorone diisocyanate and dibutyltin dilaurate, stir and mix well to obtain a mixed solution; S3.2: Under the protection of nitrogen, the mixed solution is heated at 70-80° C. for 3-4 hours for reflux reaction to obtain an intermediate; S3.3: Adjust the heating temperature to 50-60°C, add hydroxyethyl acrylate to the above intermediate, continue to keep the reaction warm for 2-3 hours, add p-hydroxyanisole, stir and mix evenly, filter and distill under reduced pressure to obtain an acrylate prepolymer.

[0011] Furthermore, S4 specifically includes the following steps: S4.1: adding the acrylate prepolymer prepared in step S3.3 to toluene in a mass ratio of 1:(1-3), stirring and dissolving, to obtain an acrylate prepolymer solution; S4.2: Under the protection of nitrogen, add histamine to the above acrylate prepolymer solution at a solid-liquid ratio of 1g:(18-22)mL, stir and mix evenly, then add N,N'-dicyclohexylcarbodiimide at a solid-liquid ratio of 1g:(230-240)mL, and heat and stir at 60-70°C for 2-4h to obtain a mixed reaction solution; S4.3: adding anhydrous magnesium sulfate to the above mixed reaction liquid, removing water, filtering and distilling under reduced pressure to remove insoluble impurities and solvent, and obtaining a modified prepolymer.

[0012] Furthermore, the volume ratio of deionized water to the total amount of titanium source solution and zinc source solution in step S1.2 is 1:(6-8), and the mass ratio of sodium silicate and cerium sulfate to nanocomposite powder in step S1.5 is (3-5):1:(45-55).

[0013] Furthermore, the raw material components of the acrylate prepolymer include, by mass, 90-100 parts of polyester polyol, 40-50 parts of isophorone diisocyanate, 20-25 parts of hydroxyethyl acrylate, 1-2 parts of dibutyltin dilaurate, 1-2 parts of p-hydroxyanisole and 120-130 parts of toluene.

[0014] Furthermore, the printing ink comprises, by weight: 40-50 parts of modified prepolymer, 10-20 parts of isobornyl acrylate, 10-15 parts of trimethylolpropane triacrylate, 5-10 parts of photoinitiator, 8-10 parts of pigment, 10-20 parts of surface modified nanocomposite powder, 8-10 parts of composite anti-aging agent and 2-5 parts of auxiliary agent; wherein the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of (1-2):1.

[0015] Furthermore, the additives include, by weight: 0.5-1.5 parts of a leveling agent, 0.5-1.5 parts of a defoaming agent, and 1-2 parts of a dispersant; wherein the leveling agent is a polyether-modified polydimethylsiloxane leveling agent, the defoaming agent is an organosilicon defoaming agent, and the dispersant is a high molecular weight block copolymer dispersant.

[0016] Furthermore, a high-adhesion LED-UV metal printing ink is prepared by any of the above-mentioned methods for preparing a high-adhesion LED-UV metal printing ink.

[0017] Compared with the prior art, the present invention has at least the following beneficial effects: 1. The present invention first uses tetrabutyl titanate and zinc nitrate hexahydrate as raw materials, utilizes a sol-gel method to prepare a binary mixed gel, and then calcines the mixed gel at a high temperature to prepare a nano-composite powder with anti-ultraviolet performance, and then adjusts the nano-composite powder into a slurry, and adds a sodium silicate solution and cerium sulfate to react, and performs surface modification on the nano-composite powder. On the one hand, the modification of silicon and cerium can change the surface properties of the nano-composite powder, reduce the interaction between nanoparticles, make it more oleophilic, and thus improve the dispersibility of the nano-composite powder in ink. On the other hand, the modification of silicon and cerium can effectively capture photogenerated electrons or holes, promote the separation of electron-hole pairs, reduce the occurrence of photocatalytic reactions, and achieve the effect of inhibiting the photocatalytic activity of the nano-composite powder. Therefore, after the surface-modified nano-composite powder is added to the ink, the aging resistance of the ink can be effectively improved, which is beneficial to the improvement of the anti-discoloration performance of the ink.

[0018] 2. The present invention prepares a composite anti-aging agent by dissolving copper sulfate pentahydrate and kaempferol separately, mixing them for hydrothermal reaction, and adding the composite anti-aging agent to ink. On the one hand, the composite anti-aging agent can remove free radicals, prevent the chain reaction caused by free radicals, and delay the aging process of the ink. On the other hand, the composite anti-aging agent can not only absorb ultraviolet energy and convert it into heat energy or other forms of energy, thereby reducing the damage of ultraviolet rays to organic components in the ink, but also form a physical barrier in the ink to block the penetration of ultraviolet rays and protect other components in the ink from the influence of ultraviolet rays. In addition, the addition of the composite anti-aging agent can produce a synergistic effect with the surface-modified nano-composite powder to further improve the anti-ultraviolet aging performance of the ink.

[0019] 3. The present invention prepares an acrylate prepolymer by first using isophorone diisocyanate, polyester polyol and hydroxyethyl acrylate as raw materials, and then reacts the acrylate prepolymer with histamine under the catalysis of N,N'-dicyclohexylcarbodiimide to graft histamine into the molecular chain of the acrylate prepolymer. Since the polar groups in the histamine molecules can form hydrogen bonds, coordination bonds and covalent bonds with the metal surface, the interface interaction and chemical bonding are enhanced, thereby effectively improving the adhesion of the prepared printing ink to different metal materials, thereby improving its applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0021] Figure 1 This is a flow chart of a method for preparing a high-adhesion LED-UV metal printing ink used in an embodiment of the present invention. DETAILED DESCRIPTION

[0022] A high-adhesion LED-UV metal printing ink and a preparation method thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and specific embodiments. Example 1

[0023] A method for preparing a high-adhesion LED-UV metal printing ink, such as Figure 1 As shown, the following steps are included: S1: Preparation of surface modified nanocomposite powders S1.1: Add tetrabutyl titanate and zinc nitrate hexahydrate into anhydrous ethanol at a volume ratio of 1:8 and a solid-liquid ratio of 1g:15mL, respectively, and stir and dissolve to obtain a titanium source solution and a zinc source solution; S1.2: Control the molar ratio of Ti to Zn to be 1:3, add the titanium source solution to the zinc source solution while stirring, continue stirring for 20 minutes, add deionized water after sufficient mixing, and add glacial acetic acid to adjust the pH to 6.6, continue stirring for 20 minutes, and then stand for aging for 8 hours to obtain a mixed gel, wherein the volume ratio of deionized water to the total amount of the titanium source solution and the zinc source solution is 1:6; S1.3: The mixed gel is placed in an oven and dried at 80°C for 3 h, and then placed in a muffle furnace and calcined at 500°C for 2 h. After grinding and sieving, a nanocomposite powder is obtained; S1.4: Add the above nanocomposite powder into deionized water at a mass ratio of 1:3, ultrasonically disperse for 30 minutes, and then add sodium hydroxide to adjust the pH to 9 to obtain a nanocomposite slurry; S1.5: The nanocomposite slurry is heated to 80°C and kept warm, and then a 1.2 mol / L sodium silicate solution is added while stirring, and after standing and aging for 1 hour, the heating temperature is adjusted to 65°C, and cerium sulfate is added while stirring, and then standing and aging for 4 hours, and then filtered, washed and dried to obtain a surface-modified nanocomposite powder, wherein the mass ratio of sodium silicate and cerium sulfate to the nanocomposite powder is 3:1:45; S2: Preparation of composite anti-aging agent S2.1: Add copper sulfate pentahydrate into deionized water at a solid-liquid ratio of 1g:40mL, and stir thoroughly at a rate of 500r / min to dissolve to obtain a copper sulfate solution; S2.2: Add kaempferol to 75% ethanol solution at a solid-liquid ratio of 1 g:200 mL, and stir thoroughly at a rate of 400 r / min to dissolve, to obtain a kaempferol solution; S2.3: Add the above kaempferol solution to an equal volume of the above copper sulfate solution, stir and mix thoroughly, then add 1 mol / L sodium hydroxide solution to adjust the pH to 7, heat and react at 50°C for 4h, centrifuge, wash and dry to obtain a composite anti-aging agent; S3: Preparation of acrylate prepolymer S3.1: Add 90 parts by weight of polyester polyol to 120 parts by weight of toluene, stir thoroughly to dissolve, then add 40 parts by weight of isophorone diisocyanate and 1 part by weight of dibutyltin dilaurate, stir and mix well to obtain a mixed solution; S3.2: Under the protection of nitrogen, the mixed solution is heated at 70° C. for 3 h for reflux reaction to obtain an intermediate; S3.3: Adjust the heating temperature to 50°C, add 20 parts by weight of hydroxyethyl acrylate to the intermediate, continue to keep the reaction warm for 2 hours, add 1 part by weight of p-hydroxyanisole, stir and mix evenly, filter and distill under reduced pressure to obtain an acrylate prepolymer; S4: Preparation of modified prepolymer S4.1: adding the acrylate prepolymer obtained in step S3.3 into toluene at a mass ratio of 1:1, stirring and dissolving, to obtain an acrylate prepolymer solution; S4.2: Under the protection of nitrogen, histamine was added to the above acrylate prepolymer solution at a solid-liquid ratio of 1g:18mL, and after stirring and mixing evenly, N,N'-dicyclohexylcarbodiimide was added at a solid-liquid ratio of 1g:230mL, and heated and stirred at 60°C for 2h to obtain a mixed reaction liquid; S4.3: adding anhydrous magnesium sulfate to the mixed reaction liquid to remove water, filtering and distilling under reduced pressure to remove insoluble impurities and solvent to obtain a modified prepolymer; S5: Mixing and preparation of printing ink By weight, 40 parts of the above-mentioned modified prepolymer, 10 parts of isobornyl acrylate, 10 parts of trimethylolpropane triacrylate, 5 parts of photoinitiator, 8 parts of pigment, 10 parts of the above-mentioned surface modified nano-composite powder, 8 parts of the above-mentioned composite anti-aging agent, 0.5 parts of polyether modified polydimethylsiloxane leveling agent, 0.5 parts of silicone defoaming agent and 1 part of high molecular weight block copolymer dispersant are fully stirred and mixed to obtain printing ink. Example 2

[0024] A method for preparing a high-adhesion LED-UV metal printing ink, such as Figure 1 As shown, the following steps are included: S1: Preparation of surface modified nanocomposite powders S1.1: Add tetrabutyl titanate and zinc nitrate hexahydrate into anhydrous ethanol at a volume ratio of 1:9 and a solid-liquid ratio of 1g:20mL, respectively, and stir and dissolve to obtain a titanium source solution and a zinc source solution; S1.2: Control the molar ratio of Ti to Zn to be 1:4, add the titanium source solution to the zinc source solution while stirring, continue stirring for 25 minutes, add deionized water after sufficient mixing, and add glacial acetic acid to adjust the pH to 6.7, continue stirring for 25 minutes, and then stand for aging for 9 hours to obtain a mixed gel, wherein the volume ratio of deionized water to the total amount of the titanium source solution and the zinc source solution is 1:7; S1.3: The mixed gel is placed in an oven and dried at 90°C for 4 hours, and then placed in a muffle furnace and calcined at 550°C for 2.5 hours. After grinding and sieving, a nanocomposite powder is obtained; S1.4: Add the above nanocomposite powder into deionized water at a mass ratio of 1:3.5, ultrasonically disperse for 35 minutes, and then add sodium hydroxide to adjust the pH to 9.5 to obtain a nanocomposite slurry; S1.5: The nanocomposite slurry is heated to 85°C and kept warm, and then a 1.25 mol / L sodium silicate solution is added while stirring, and after standing and aging for 1.5 hours, the heating temperature is adjusted to 70°C, and cerium sulfate is added while stirring, and then standing and aging for 4.5 hours, and then filtered, washed and dried to obtain a surface-modified nanocomposite powder, wherein the mass ratio of sodium silicate and cerium sulfate to the nanocomposite powder is 4:1:50; S2: Preparation of composite anti-aging agent S2.1: Add copper sulfate pentahydrate into deionized water at a solid-liquid ratio of 1g:45mL, and stir and dissolve at a rate of 550r / min to obtain a copper sulfate solution; S2.2: Add kaempferol to 75% ethanol solution at a solid-liquid ratio of 1 g:250 mL, and stir thoroughly at a rate of 450 r / min to dissolve, to obtain a kaempferol solution; S2.3: Add the above kaempferol solution to an equal volume of the above copper sulfate solution, stir and mix thoroughly, then add 1 mol / L sodium hydroxide solution to adjust the pH to 7.5, heat and react at 55°C for 4.5h, centrifuge, wash and dry to obtain a composite anti-aging agent; S3: Preparation of acrylate prepolymer S3.1: Add 95 parts by weight of polyester polyol to 125 parts by weight of toluene, stir thoroughly to dissolve, then add 45 parts by weight of isophorone diisocyanate and 1.5 parts by weight of dibutyltin dilaurate, stir and mix well to obtain a mixed solution; S3.2: Under the protection of nitrogen, the mixed solution was heated at 75°C for 3.5 hours for reflux reaction to obtain an intermediate; S3.3: Adjust the heating temperature to 55°C, add 22.5 parts by weight of hydroxyethyl acrylate to the intermediate, continue to keep the reaction warm for 2.5 hours, add 1.5 parts by weight of p-hydroxyanisole, stir and mix evenly, filter and distill under reduced pressure to obtain an acrylate prepolymer; S4: Preparation of modified prepolymer S4.1: adding the acrylate prepolymer obtained in step S3.3 into toluene at a mass ratio of 1:2, stirring and dissolving, to obtain an acrylate prepolymer solution; S4.2: Under the protection of nitrogen, histamine was added to the above acrylate prepolymer solution at a solid-liquid ratio of 1g:20mL, and after stirring and mixing evenly, N,N'-dicyclohexylcarbodiimide was added at a solid-liquid ratio of 1g:235mL, and heated and stirred at 65°C for 3h to obtain a mixed reaction solution; S4.3: adding anhydrous magnesium sulfate to the mixed reaction liquid to remove water, filtering and distilling under reduced pressure to remove insoluble impurities and solvent to obtain a modified prepolymer; S5: Mixing and preparation of printing ink By weight, 45 parts of the above-mentioned modified prepolymer, 15 parts of isobornyl acrylate, 12.5 parts of trimethylolpropane triacrylate, 7.5 parts of photoinitiator, 9 parts of pigment, 15 parts of the above-mentioned surface-modified nano-composite powder, 9 parts of the above-mentioned composite anti-aging agent, 1 part of polyether modified polydimethylsiloxane leveling agent, 1 part of silicone defoaming agent and 1.5 parts of high molecular weight block copolymer dispersant are fully stirred and mixed to obtain printing ink. Example 3

[0025] A method for preparing a high-adhesion LED-UV metal printing ink, such as Figure 1 As shown, the following steps are included: S1: Preparation of surface modified nanocomposite powders S1.1: Add tetrabutyl titanate and zinc nitrate hexahydrate into anhydrous ethanol at a volume ratio of 1:10 and a solid-liquid ratio of 1g:25mL, respectively, and stir to dissolve to obtain a titanium source solution and a zinc source solution; S1.2: Control the molar ratio of Ti to Zn to be 1:5, add the titanium source solution to the zinc source solution while stirring, continue stirring for 30 minutes, add deionized water after sufficient mixing, and add glacial acetic acid to adjust the pH to 6.8, continue stirring for 30 minutes, and then stand for aging for 10 hours to obtain a mixed gel, wherein the volume ratio of deionized water to the total amount of the titanium source solution and the zinc source solution is 1:8; S1.3: The mixed gel is placed in an oven and dried at 100°C for 5 h, and then placed in a muffle furnace and calcined at 600°C for 3 h. After grinding and sieving, a nanocomposite powder is obtained; S1.4: Add the above nanocomposite powder into deionized water at a mass ratio of 1:4, ultrasonically disperse for 40 minutes, and then add sodium hydroxide to adjust the pH to 10 to obtain a nanocomposite slurry; S1.5: The nanocomposite slurry is heated to 90°C and kept warm, and then a 1.3 mol / L sodium silicate solution is added while stirring, and after standing and aging for 2 hours, the heating temperature is adjusted to 75°C, and cerium sulfate is added while stirring, and then standing and aging for 5 hours, and then filtered, washed and dried to obtain a surface-modified nanocomposite powder, wherein the mass ratio of sodium silicate and cerium sulfate to the nanocomposite powder is 5:1:55; S2: Preparation of composite anti-aging agent S2.1: Add copper sulfate pentahydrate into deionized water at a solid-liquid ratio of 1g:50mL, and stir thoroughly at a rate of 600r / min to dissolve to obtain a copper sulfate solution; S2.2: Add kaempferol to 75% ethanol solution at a solid-liquid ratio of 1 g:300 mL, and stir to dissolve at a rate of 500 r / min to obtain a kaempferol solution; S2.3: Add the above kaempferol solution to an equal volume of the above copper sulfate solution, stir and mix thoroughly, then add 1 mol / L sodium hydroxide solution to adjust the pH to 8, heat and react at 60°C for 5h, centrifuge, wash and dry to obtain a composite anti-aging agent; S3: Preparation of acrylate prepolymer S3.1: Add 100 parts by weight of polyester polyol to 130 parts by weight of toluene, stir thoroughly to dissolve, then add 50 parts by weight of isophorone diisocyanate and 2 parts by weight of dibutyltin dilaurate, stir and mix well to obtain a mixed solution; S3.2: Under the protection of nitrogen, the mixed solution is heated at 80° C. for 4 h for reflux reaction to obtain an intermediate; S3.3: Adjust the heating temperature to 60°C, add 25 parts by weight of hydroxyethyl acrylate to the intermediate, continue to keep the reaction warm for 3 hours, add 2 parts by weight of p-hydroxyanisole, stir and mix evenly, filter and distill under reduced pressure to obtain an acrylate prepolymer; S4: Preparation of modified prepolymer S4.1: adding the acrylate prepolymer obtained in step S3.3 into toluene at a mass ratio of 1:3, stirring and dissolving, to obtain an acrylate prepolymer solution; S4.2: Under the protection of nitrogen, histamine was added to the above acrylate prepolymer solution at a solid-liquid ratio of 1g:22mL, and after stirring and mixing evenly, N,N'-dicyclohexylcarbodiimide was added at a solid-liquid ratio of 1g:240mL, and heated and stirred at 70°C for 4h to obtain a mixed reaction liquid; S4.3: adding anhydrous magnesium sulfate to the mixed reaction liquid to remove water, filtering and distilling under reduced pressure to remove insoluble impurities and solvent to obtain a modified prepolymer; S5: Mixing and preparation of printing ink By weight, 50 parts of the above-mentioned modified prepolymer, 20 parts of isobornyl acrylate, 15 parts of trimethylolpropane triacrylate, 10 parts of photoinitiator, 10 parts of pigment, 20 parts of the above-mentioned surface modified nano-composite powder, 10 parts of the above-mentioned composite anti-aging agent, 1.5 parts of polyether modified polydimethylsiloxane leveling agent, 1.5 parts of silicone defoaming agent and 2 parts of high molecular weight block copolymer dispersant are fully stirred and mixed to obtain printing ink.

[0026] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the surface modified nanocomposite powder in step S5 is removed.

[0027] Comparative Example 2 The difference between this comparative example 2 and example 1 is that steps S1.4-1.5 are removed, and the surface-modified nanocomposite powder in step S5 is replaced by an equal amount of the nanocomposite powder prepared in step S1.3.

[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the composite anti-aging agent in step S5 is removed.

[0029] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the composite anti-aging agent in step S5 is replaced by an equal amount of surface-modified nano-composite powder.

[0030] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the surface modified nano-composite powder in step S5 is replaced by an equal amount of composite anti-aging agent.

[0031] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the modified prepolymer in step S5 is replaced by an equal amount of the acrylate prepolymer prepared in step S3.3.

[0032] Test Case Test 1: The printing inks prepared in Examples 1-3 and Comparative Examples 1-5 were coated on the surface of an iron plate using a screen printing machine, and cured by LED-UV light to form a coating to obtain a sample. Then, referring to GB / T 16422.3-2022 standard, each sample was placed in an ultraviolet aging tester for an ultraviolet artificial accelerated aging test. The color difference ΔE of the sample coating was tested according to GB / T11186.2-1989 standard and GB / T11186.3-1989 standard. The results are shown in Table 1.

[0033] Table 1: Comparison of color difference results of UV aging test samples

[0034] As can be seen from Table 1, after the surface modified nanocomposite powder is removed in Comparative Example 1, the color difference of the coating of the obtained printing ink after the UV aging test is about 17.74, which is much higher than that of Example 1. It can be seen that after the surface modified nanocomposite powder is added to the ink, the aging resistance of the ink can be effectively improved, which is beneficial to the improvement of the anti-discoloration performance of the ink; When the nano-composite powder is not surface modified in Comparative Example 2, the color difference of the coating of the prepared printing ink after the UV aging test is about 11.28, which is also higher than that of Example 1. It can be seen that by adjusting the nano-composite powder into a slurry, adding sodium silicate solution and cerium sulfate to react, and surface modifying the nano-composite powder, the photocatalytic activity of the nano-composite powder can be inhibited, thereby further improving its anti-ultraviolet aging performance.

[0035] After the composite anti-aging agent is removed in Comparative Example 3, the color difference of the coating of the obtained printing ink after the ultraviolet aging test is about 10.74, which is lower than that of Example 1, indicating that the addition of the composite anti-aging agent can improve the anti-ultraviolet aging performance of the ink, thereby delaying the aging of the ink.

[0036] When only a single surface-modified nano-composite powder and a single composite anti-aging agent are added to Comparative Examples 4 and 5, the color difference of the coating of the prepared printing ink after the UV aging test is approximately 8.87 and 10.36, respectively, which are higher than that of Example 1. It can be seen that the surface-modified nano-composite powder and the composite anti-aging agent have a synergistic effect, and the combination of the two can further improve the anti-ultraviolet aging performance of the ink, thereby achieving the effect of further delaying the aging of the ink.

[0037] Test 2: The printing inks prepared in Examples 1-3 and Comparative Example 6 were respectively coated on the surfaces of different metal plates (iron, copper, aluminum, steel) using a screen printing machine. After being cured by LED-UV light, samples were obtained. Adhesion tests were then carried out in accordance with GB / T9286-1998. The results are shown in Table 2.

[0038] Table 2: Comparison of adhesion results on different metal plate surfaces

[0039] It can be seen from Table 2 that when the acrylate prepolymer is not modified in Comparative Example 6, the adhesion of the obtained printing ink to the iron plate, copper plate, aluminum plate and steel plate are level 3, level 3, level 2 and level 3, respectively, which are all worse than that of Example 1. This shows that grafting histamine into the molecular chain of the acrylate prepolymer can effectively improve the adhesion of the obtained printing ink to different metal materials, thereby improving its applicability.

[0040] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a high-adhesion LED-UV metal printing ink, characterized in that: The steps include: S1: Preparation of surface modified nanocomposite powders The nanocomposite powder is prepared by using tetrabutyl titanate and zinc nitrate hexahydrate as raw materials, and then the nanocomposite powder is adjusted into a slurry, and a sodium silicate solution and cerium sulfate are added to react to obtain a surface-modified nanocomposite powder; S2: Preparation of composite anti-aging agent Copper sulfate pentahydrate and kaempferol are dissolved separately, mixed and heated for reaction, and a composite anti-aging agent is prepared; S3: Preparation of acrylate prepolymer The acrylate prepolymer is prepared by reacting polyester polyol, isophorone diisocyanate, hydroxyethyl acrylate, dibutyltin dilaurate and p-hydroxyanisole as raw materials; S4: Preparation of modified prepolymer The acrylate prepolymer is dissolved in toluene, histamine and N,N'-dicyclohexylcarbodiimide are added, heated to react, dried, filtered and distilled under reduced pressure to obtain a modified prepolymer; S5: Mixing and preparation of printing ink The modified prepolymer, isobornyl acrylate, trimethylolpropane triacrylate, photoinitiator, pigment, the surface modified nano composite powder, the composite anti-aging agent and auxiliary agent are fully stirred and mixed to obtain printing ink.

2. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 1, characterized in that: S1 includes the following steps: S1.1: Add tetrabutyl titanate and zinc nitrate hexahydrate into anhydrous ethanol at a volume ratio of 1:(8-10) and a solid-liquid ratio of 1g:(15-25)mL, respectively, and stir thoroughly to dissolve to obtain a titanium source solution and a zinc source solution; S1.2: Control the molar ratio of Ti to Zn to be 1:(3-5), add the titanium source solution to the zinc source solution while stirring, continue stirring for 20-30 minutes, add deionized water after thorough mixing, and add glacial acetic acid to adjust the pH to 6.6-6.8, continue stirring for 20-30 minutes, and then stand for aging for 8-10 hours to obtain a mixed gel; S1.3: placing the mixed gel in an oven, drying at 80-100°C for 3-5h, and then placing it in a muffle furnace, calcining at 500-600°C for 2-3h, grinding and sieving to obtain a nanocomposite powder; S1.4: Add the above nanocomposite powder into deionized water in a mass ratio of 1:(3-4), ultrasonically disperse for 30-40 minutes, and then add sodium hydroxide to adjust the pH to 9-10 to obtain a nanocomposite slurry; S1.5: Heat the above nanocomposite slurry to 80-90°C and keep it warm, then add 1.2-1.3 mol / L sodium silicate solution while stirring, let it stand for 1-2 hours, adjust the heating temperature to 65-75°C, add cerium sulfate while stirring, let it stand for 4-5 hours, filter, wash and dry to obtain a surface-modified nanocomposite powder.

3. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 2, characterized in that: S2 includes the following steps: S2.1: Add copper sulfate pentahydrate into deionized water at a solid-liquid ratio of 1 g: (40-50) mL, and stir and dissolve at a rate of 500-600 r / min to obtain a copper sulfate solution; S2.2: Add kaempferol to 75% ethanol solution at a solid-liquid ratio of 1 g: (200-300) mL, and stir thoroughly at a rate of 400-500 r / min to dissolve, to obtain a kaempferol solution; S2.3: Add the above-mentioned kaempferol solution to an equal volume of the above-mentioned copper sulfate solution, stir and mix thoroughly, then add 1 mol / L sodium hydroxide solution to adjust the pH to 7-8, and heat the reaction at 50-60°C for 4-5h. After centrifugal separation, washing and drying, a composite anti-aging agent is obtained.

4. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 3, characterized in that: S3 includes the following steps: S3.1: Add polyester polyol to toluene, stir thoroughly to dissolve, then add isophorone diisocyanate and dibutyltin dilaurate, stir and mix well to obtain a mixed solution; S3.2: Under the protection of nitrogen, the mixed solution is heated at 70-80° C. for 3-4 hours for reflux reaction to obtain an intermediate; S3.3: Adjust the heating temperature to 50-60°C, add hydroxyethyl acrylate to the above intermediate, continue to keep the reaction warm for 2-3 hours, add p-hydroxyanisole, stir and mix evenly, filter and distill under reduced pressure to obtain an acrylate prepolymer.

5. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 4, characterized in that: S4 specifically includes the following steps: S4.1: adding the acrylate prepolymer prepared in step S3.3 to toluene in a mass ratio of 1:(1-3), stirring and dissolving, to obtain an acrylate prepolymer solution; S4.2: Under the protection of nitrogen, add histamine to the above acrylate prepolymer solution at a solid-liquid ratio of 1g:(18-22)mL, stir and mix evenly, then add N,N'-dicyclohexylcarbodiimide at a solid-liquid ratio of 1g:(230-240)mL, and heat and stir at 60-70°C for 2-4h to obtain a mixed reaction solution; S4.3: adding anhydrous magnesium sulfate to the above mixed reaction liquid, removing water, filtering and distilling under reduced pressure to remove insoluble impurities and solvent, and obtaining a modified prepolymer.

6. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 2, characterized in that: The volume ratio of deionized water to the total amount of titanium source solution and zinc source solution in step S1.2 is 1:(6-8), and the mass ratio of sodium silicate and cerium sulfate to nanocomposite powder in step S1.5 is (3-5):1:(45-55).

7. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 4, characterized in that: The raw material components of the acrylate prepolymer include, by mass, 90-100 parts of polyester polyol, 40-50 parts of isophorone diisocyanate, 20-25 parts of hydroxyethyl acrylate, 1-2 parts of dibutyltin dilaurate, 1-2 parts of p-hydroxyanisole and 120-130 parts of toluene.

8. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 5, characterized in that: The printing ink comprises, by weight: 40-50 parts of modified prepolymer, 10-20 parts of isobornyl acrylate, 10-15 parts of trimethylolpropane triacrylate, 5-10 parts of photoinitiator, 8-10 parts of pigment, 10-20 parts of surface modified nanocomposite powder, 8-10 parts of composite anti-aging agent and 2-5 parts of auxiliary agent; wherein the photoinitiator is composed of 2-hydroxy-2-methyl-1-phenyl-1-propanone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in a mass ratio of (1-2):

1.

9. The method for preparing a high-adhesion LED-UV metal printing ink according to claim 1, characterized in that: In parts by weight, the additives include: 0.5-1.5 parts of leveling agent, 0.5-1.5 parts of defoaming agent and 1-2 parts of dispersing agent; wherein the leveling agent is a polyether modified polydimethylsiloxane leveling agent, the defoaming agent is an organosilicon defoaming agent, and the dispersing agent is a high molecular weight block copolymer dispersing agent.

10. A high-adhesion LED-UV metal printing ink, characterized in that: The ink is prepared by the method for preparing a high-adhesion LED-UV metal printing ink according to any one of claims 1 to 9.